Application of Enterprise Risk Management to Banking Risk - Hasan, Nida Nadya; Rahmadini, Fatiah; Dariyah, Dariyah (Economics and Business Faculty UNUSIA, 2021)
Abstract The implementation of Enterprise Risk Management (ERM) proactively determines the appropriate type and level of risk to achieve the organization's strategic objectives and assists management in understanding and managing all company business risks using an integrated structure and coordinated management. Although risks cannot be completely avoided or eliminated, they can be managed and minimized with an integrated risk management system. The purpose of this study is to prove whether the application of ERM can minimize credit risk, interest rate risk, and liquidity risk in banking companies and whether the internal audit function can strengthen the effect of ERM implementation in minimizing the risks faced by banks. The sample of this research is banks listed on the Indonesia Stock Exchange in 2011-2016. The results of this study indicate that the application of ERM for banks is not proven to have an effect in minimizing credit risk, interest rate risk, and liquidity risk. ERM does not manage risk individually but manages risk collectively so that it can identify company activities that contribute the most to the company's total risk and mitigation is carried out, and ERM is a process designed to manage risk so that it is at optimal risk that does not endanger the banking business, and management tends to take risks to optimize the profits to be obtained and companies tend to dare to take risks if the risk is not at a level that endangers the banking business condition. The internal audit function also has no effect in strengthening the relationship between ERM implementation and credit risk, interest rate risk, and liquidity risk.